Novel Angiotensin-I Converting Enzyme Inhibitory Peptides Isolated From Rice Wine Lees: Purification, Characterization, and Structure-Activity Relationship - He, Zeqi; Liu, Guo; Qiao, Zijiao; Cao, Yong; Song, Mingyue (Frontiers in Nutrition, 2021)
Peptides inhibiting Angiotensin-I converting enzyme (ACE, EC. 3.4.15.1) are possible cures of hypertension. Food-derived ACE-inhibitory peptides are popular because of their reduced side effects. In this work, we report steps for purifying ACE-inhibitory peptides from the lees of traditional Chinese rice wine and describe the product’s biochemical properties. After three steps of reversed-phase high-performance liquid chromatography (RP-HPLC), we identified two peptides: LIIPQH and LIIPEH. Both peptides showed excellent ACE-inhibitory activity (IC50 values of 120.10±9.31 μg/mL and 60.49±5.78 μg/mL), were characterized as mixed-type ACE inhibitors and were stable against both ACE and gastrointestinal enzymes. This is the first time that food-derived ACE-inhibitory LIIPQH and LIIPEH been reported. The present study suggests that a significant amount of the lees produced as a by-product when rice is used in liquor-making can be utilized in various fields related to functional foods and medicine. So, it is necessary to make much more effective use of underutilized resources, including lees.